Induction of organ dysfunction and up-regulation of inflammatory markers in the liver and kidneys of hypotensive brain dead rats: a model to study marginal organ donors. - van der Hoeven, J; Ploeg, R; Postema, F; Molema, I; de Vos, P; Girbes, A; van Suylichem, P; van Schilfgaarde, R; Ter Horst, G (1999)
BACKGROUND: Marginal donors exposed to the full array of effects induced by brain death are characterized by low success rates after transplantation. This study examined whether organs from marginal brain dead animals show any change in organ function or tissue activation making them eventually more susceptible for additional damage during preservation and transplantation. METHODS: To study this hypothesis we first focused on effects of brain death on donor organ quality by using a brain death model in the rat. After induction of brain death, Wistar rats were ventilated for 1 and 6 hr and then killed. Sham-operated rats served as controls. Organ function was studied using standard serum parameters. Tissue activation of liver and kidney was assessed by staining of immediate early gene products (IEG: FOS, JUN), and inflammatory markers; cell adhesion molecules (Intercellular adhesion molecule-1, vascular cell adhesion molecule-1), leukocyte infiltrates (CD45, T cell receptor, CD8, CD4), and MHC class II. RESULTS: During brain death progressive organ dysfunction was observed that coincided with a significant increase in activation of immediate early genes, intercellular adhesion molecule-1, vascular cell adhesion molecule-1, CD45, and MHC class II versus nonbrain dead controls. In liver tissue also the markers for T cell receptor and CD8 significantly increased. CONCLUSIONS: These findings suggest that an immune activation with increased endothelial cell activation and immediate early gene expression occurs in marginal donors after brain death induction. We suggest that brain death should not longer be regarded as a given nondeleterious condition but as a dynamic process with potential detrimental effects on donor organs that could predispose grafts for increased alloreactivity after transplantation.